Open achilles tendon rupture - Che Ahmad, Aminudin; Awang, Mohd Shukrimi; Mohd Yusof, Nazri; Mohd Amin, Azril; Khalid, Kamarul Ariffin (2007)
Achilles tendon rupture is a not uncommon injury, however, the incidence of open Achilles tendon injury is frequently reported. It is generally perceived that open Achilles tendon injury is associated with a poor outcome and severe complications. In this study, we review the demographic feature of open Achilles injury and their functional outcome following surgical intervention. A retrospective investigation was done at Hospital Tengku Ampuan Afzan (HTAA) Kuantan, Pahang from January 2001 until December 2005. Universal sampling was used to include all open Achilles tendon rupture cases. We reviewed the records of these patients as well as performing clinical assessment of the. We reviewed demographic data, the etiology of the injury and the functional outcome using the Olerud and Molander scoring system. Patients were asked about satisfaction to the current condition either through the telephone or during follow-up. Thirty three patients were available for review (26 male and 7 female patients). Their aged range from 12 to 8 years old. Toilet bowl injury is the common cause of these open injury (23 cases, 68%) followed by motor vehicle accidents (6 cases, 21%). Excellent and good outcome were achieved in 69% cases. Operative treatment of open Achilles tendon rupture restores sufficient ankle function and a significant percentage of patients has excellent and good outcome. Early intervention, proper debridement and good antibiotic coverage are important to ensure the outcome. Some sort of prevention is required to reduce the rate of toilet bowl injuries resulting in open Achilles tendon injuries.